HEALTH CARE OF PATIENTS WITH INFLAMMATORY BOWEL DISEASES - Pavić, Katarina; Bogdanović Vasić, Slobodanka; Vešić, Marija; Antonić, Roland; Perović, Dušica; Savić, Nikola (HEALTH CARE, 2024)
Inflammatory bowel diseases are chronic diseases of unknown etiology with a tendency to occur in the younger population. There are two types of disease - Crohn's disease and ulcerative colitis. Due to their complexity, these diseases represent a major problem of today's medicine, both from diagnostic and therapeutic aspects. Inflammatory bowel diseases negatively affect the quality of life, education, employment and daily functioning of patients. This paper presents the most common problems that nurses/technicians in hospital conditions encounter when working with patients, through the method of the health care process, with the listed nursing interventions for the specific problem.
Keywords: inflammatory bowel diseases, Crohn’s disease, ulcerative colitis,nursing process